Virus-Like Particles Derived From a Virulent Strain of Pest des Petits Ruminants Virus Elicit a More Vigorous Immune Response in Mice and Small Ruminants Than Those From a Vaccine Strain - Yan, Feihu; Li, Entao; Li, Ling; Schiffman, Zachary; Huang, Pei; Zhang, Shengnan; Li, Guohua; Jin, Hongli; Wang, Hualei; Zhang, Xinghai; Gao, Yuwei; Feng, Na; et al. (Frontiers in Microbiology, 2020)
Peste des petits ruminants (PPRs) is highly contagious, acute or subacute disease of small ruminants caused by peste des petits ruminants virus (PPRV). To date, several studies have designed and evaluated PPRV-like particles (VLPs) as a vaccine candidate for the prevention and control of PPR, with the majority of these VLPs constructed using sequences derived from a PPRV vaccine strain due to its high immunogenicity. However, because of the lack of available genetic material and certain structural proteins and/or the alteration of posttranslational glycosylation modifications, the immunogenicity of VLPs derived from a vaccine strain is not always optimal. In this study, two PPRV VLP candidates, derived from either the lineage IV Tibet/30 virulent strain or the lineage II Nigeria 75/1 vaccine strain, were generated using a baculovirus system through the coexpression of the PPRV matrix (M), hemagglutinin (H), and fusion (F) proteins in the high expression level cell line High Five. These VLPs were then used to immunize mice, goats, and sheep followed by two boosts after primary immunization. Both VLPs were found to induce a potent humoral immune response as demonstrated by the high ratio of immunoglobulin G1 (IgG1) to IgG2a. In all animals, both VLPs induced high titers of virus-neutralizing antibodies (VNAs), as well as H- and F-specific antibodies, with the Tibet/30 VLPs yielding higher antibody titers by comparison to the Nigeria 75/1 VLPs. Studies in mice also demonstrated that the Tibet/30 VLPs induced a more robust interleukin 4 and interferon γ response than the Nigeria 75/1 VLPs. Goats and sheep immunized with both VLPs exhibited a robust humoral and cell-mediated immune response. Furthermore, our results demonstrated that the VLPs derived from the virulent lineage IV Tibet/30 strain were more immunogenic, inducing a more potent and robust humoral and cell-mediated immune response in vaccinated animals by comparison to the lineage II Nigeria 75/1 vaccine strain VLPs. In addition, VNA titers were significantly higher among animals vaccinated with the Tibet/30 VLPs by comparison to the Nigeria 75/1 VLPs. Taken together, these findings suggest that VLPs derived from the virulent lineage IV Tibet/30 strain are more immunogenic by comparison to those derived from the lineage II Nigeria 75/1 vaccine strain and thus represent a promising vaccine candidate for the control and eradication of PPR.